ANALISIS KUALITAS ES KRIM KOLANG-KALING - Siska, Indah Amelia; Faridah, Anni; Syarif, Wirnelis (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2017)
This research aims to analyze the influence of the quality of the use of kolang-Kaling as much as 10%, 15%, 20% and 25% on quality ice cream in terms of color, aroma, taste and texture. This type of research is purely experiment (true experimental) using the method of complete random design of one factor, namely the use of kolang-kaling as much as three times the repetition. The type of the data being used is the primary data sourced from 30 panelists who gave the answer to the question form (format organoleptic). The data already acquired and then ditabulasikan in the form of tables and done the analysis Variant (ANAVA). If different test followed by Duncan. Results of the research showed there were significant effects on quality of ice cream kolang-kaling cream color quality in, quality aroma kolang-kaling, quality milk aroma, soft texture quality and quality of the sweet taste but has no effect on the quality of the texture mengkirstal. It can be concluded that the percentage of the best there is on the use of kolang-kaling as much as 25% of the quality of the colour, the aroma of texture and flavor.Keywords :Kolang-Kaling, Ice Cream, Quality.